2003
DOI: 10.1037/0735-7028.34.4.406
|View full text |Cite
|
Sign up to set email alerts
|

Collaborative versus directive interventions in the treatment of eating disorders: Implications for care providers.

Abstract: Her current area of research is readiness and motivation for change in adolescents with eating disorders. SHAWNA GOODRICH received her MSW from Simmons College, Boston, MA, in 1992. She is a doctoral student in the Department of Anthropology and Sociology at the University of British Columbia. Her current research interests are critical feminist social theory and institutional enthnography. FRANCES HASTINGS received her BA in dietetics from the University of British Columbia in 1990. She works as a dietician i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 27 publications
2
35
0
Order By: Relevance
“…21 The parents' and former patient's emphasis on her own ''willpower'' and ''wish to recover'' as the most important helpful factors may indicate that motivation and ''readiness for change'' are important issues in recovering from ED. 23 Both parents viewed support from the mother as somewhat more important in overcoming ED than support from the father (Table 4). Among the helpful factors for parents, mothers rated support from friends and colleagues as significantly more important than fathers did, indicating that mothers may be more likely to make use of support from a broader social network.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…21 The parents' and former patient's emphasis on her own ''willpower'' and ''wish to recover'' as the most important helpful factors may indicate that motivation and ''readiness for change'' are important issues in recovering from ED. 23 Both parents viewed support from the mother as somewhat more important in overcoming ED than support from the father (Table 4). Among the helpful factors for parents, mothers rated support from friends and colleagues as significantly more important than fathers did, indicating that mothers may be more likely to make use of support from a broader social network.…”
Section: Resultsmentioning
confidence: 99%
“…The study did not include questions about whether patients retrospectively thought they themselves should have been allowed to influence the treatment more, or whether they evaluated positively that medical aspects of the treatment had been ''nonnegotiable''. 21,23 Further research exploring the views of patients with AN on such issues is needed.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In other populations, it has been shown that the match between patient's and therapist's expectations regarding treatment is important to the patient's motivation to change. Similar findings have emerged in eating disorders-collaborative treatment approaches were rated by both clients and therapists as more likely than directive treatment approaches to keep patients in treatment and to promote adherence with treatment recommendations (Geller, Brown, Zaitsoff, Goodrich, & Hastings, 2003). Motivational interviewing (Miller & Rollnick, 2002) was developed in order to address adherence problems and enhance readiness and motivation for recovery by, for example, combining elements of style (like warmth or empathy) and technique.…”
Section: Implications For Treatmentmentioning
confidence: 92%